Can you prove this using mathematical induction?

#1/2+2/(2^2)+3/(2^2)+...+n/(2^n)=2- (n+2)/(2^n)#

2 Answers

What you need to do is:
1) prove that it holds for #n=1#
2) prove that, if it holds for #n-1#, then it holds for #n#, where #n>1#

Explanation:

1) the first statement is easy to check, we just need to use #n=1#. Doing so, we have #1/2 = 2 - (1+2)/2^1 = 2-3/2 = 1/2#, which is true.

2) now, for the second statement, let's suppose it holds for #n-1#. If so, we have #1/2 + ... + (n-1)/2^(n-1) = 2 - ((n-1)+2)/2^(n-1)#.

Therefore, #1/2 + ... + (n-1)/2^(n-1) + n/2^n = 2 - ((n-1)+2)/2^(n-1) + n/2^n#, but we can rewrite the right hand side as

#2 - ((n-1)+2)/2^(n-1) + n/2^n = 2 - (2(n-1)+2*2-n)/2^n =#

#2 - (2*n-2+4-n)/2^n = 2 - (n+2)/2^n#//

So, by the Induction Principle, the equation holds for any #n>=1#

Hope it helps.

Oct 13, 2017

I assume there is an error in the given sum and the #3^(rd)# term should in fact read #3/2^3# rather than #3/2^2#

Induction Proof - Hypothesis

We seek to prove that:

# 1/2 + 2/2^2 + 3/2^3 + ... + n/2^n = 2-(n+2)/2^n #

Which can also be written as:

# sum_(k=1)^n \ k/2^k = 2-(n+2)/2^n # ..... [A]

So let us test this assertion using Mathematical Induction:

Induction Proof - Base case:

We will show that the given result, [A], holds for #n=1#

When #n=1# the given result gives:

# LHS = sum_(k=1)^1 \ k/2^k = 1/2^1=1/2#
# RHS = 1(4-1)/3 = 2-(1+2)/2^1 = 2-3/2 1/2 #

So the given result is true when #n=1#.

Induction Proof - General Case

Now, Let us assume that the given result [A] is true when #n=m#, for some #m in NN, m gt 1#, in which case for this particular value of #m# we have:

# sum_(k=1)^m \ k/2^k = 2-(m+2)/2^m # ..... [B]

Consider the LHS of [A] with the addition of the next term, in which case we have

# LHS = sum_(k=1)^(m+1) \ k/2^k #
# \ \ \ \ \ \ \ \ = (sum_(k=1)^(m) \ k/2^k) + (m+1)/2^(m+1) #
# \ \ \ \ \ \ \ \ = 2-(m+2)/2^m + (m+1)/2^(m+1) \ \ \ # using [B]
# \ \ \ \ \ \ \ \ = 2 - (2(m+2))/(2 * 2^m) + (m+1)/2^(m+1) #
# \ \ \ \ \ \ \ \ = 2 - (2m+4)/(2^(m+1)) + (m+1)/2^(m+1) #
# \ \ \ \ \ \ \ \ = 2 - ((2m+4)-(m+1))/(2^(m+1))#
# \ \ \ \ \ \ \ \ = 2 - ((2m+4-m-1))/(2^(m+1))#
# \ \ \ \ \ \ \ \ = 2 - (m+3)/(2^(m+1))#
# \ \ \ \ \ \ \ \ = 2 - ((m+1)+2)/(2^(m+1))#

Which is the given result [A] with #n=m+1#

Induction Proof - Summary

So, we have shown that if the given result [A] is true for #n=m#, then it is also true for #n=m+1# where #m gt 1#. But we initially showed that the given result was true for #n=1# so it must also be true for #n=2, n=3, n=4, ... # and so on.

Induction Proof - Conclusion

Then, by the process of mathematical induction the given result [A] is true for #n in NN#

Hence we have:

# 1/2 + 2/2^2 + 3/2^3 + ... + n/2^n = 2-(n+2)/2^n # QED